2013
DOI: 10.1007/s10484-013-9232-7
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Biofeedback Improves Cardiorespiratory Resting Function During Sleep

Abstract: The present study was designed to examine the effect of heart rate variability (HRV) biofeedback on the cardiorespiratory resting function during sleep in daily life. Forty-five healthy young adults were randomly assigned to one of three groups: HRV biofeedback, Autogenic Training(AT), and no-treatment control. Participants in the HRV biofeedback were instructed to use a handheld HRV biofeedback device before their habitual bedtime, those in the AT were asked to listen to an audiotaped instruction before bedti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…Using such devices might have further clarified the influence of HRV-BF on sleep. Furthermore, a previous report indicated that HRV-BF before bedtime increased respiratory sinus arrhythmia during sleep (12), but this could not be evaluated in our study because there was no HRV measurement during sleep. Second, this study population consisted of family caregivers of patients with cancer, which made it ethically difficult to include a control group.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Using such devices might have further clarified the influence of HRV-BF on sleep. Furthermore, a previous report indicated that HRV-BF before bedtime increased respiratory sinus arrhythmia during sleep (12), but this could not be evaluated in our study because there was no HRV measurement during sleep. Second, this study population consisted of family caregivers of patients with cancer, which made it ethically difficult to include a control group.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, HRV-BF with RFB may influence resting function during sleep. A previous report found healthy persons could increase respiratory sinus arrhythmia during sleep by HRV-BF before bedtime (12). Moreover, a randomized controlled trial involving an HRV-BF group and a control group investigated the use of a portable device in terms of the first night effect for healthy persons (13).…”
Section: Introductionmentioning
confidence: 99%
“…The reinforcing effect of HRV biofeedback has been well demonstrated in various studies (e.g. Lehrer, 2013, or Sakakibara et al, 2013.…”
Section: Biofeedback For Reducing Stressmentioning
confidence: 79%
“…Therefore, reduction of anxiety symptoms with HRV biofeedback, which was reported by other studies (Reiner 2008; Henriques et al 2011; Ratanasiripong et al 2012), may be particularly beneficial for postpartum women. HRV biofeedback was reported to shorten sleep latency (Ebben et al 2009), prolong deeper sleep stages (Sakakibara et al 2013), and ameliorate insomnia (McLay and Spira 2009). Due to childcare responsibilities, postpartum women sleep less during the early weeks following delivery than during pregnancy and other periods of the reproductive age (Lee et al 2000).…”
Section: Discussionmentioning
confidence: 99%